UPDATING MATHEMATICAL KNOWLEDGE WHEN SOLVING PROBLEMS - Kosybayeva У.А.; Shamataeva Н.К.; Tleubergen А.К. (Bulletin of Abai KazNPU. Series of Physical and Mathematical sciences, 2020)
The article deals with the issue of improving the methodology of teaching mathematics using new teaching methods in General education schools in the conditions of updated education. The authors characterize the implementation of the principles of didactics through teaching tools and their functions used in teaching mathematics in modern secondary schools. Among these methods, for example, the heuristic method analyzes several tasks from pages of school textbooks as an example and demonstrates learning results achieved in the same way. Using these examples, it is important for the student to analyze the problem depending on the topic of each lesson. In addition, the authors of this article analyse some peculiarities of mathematics teaching.